Alih Fungsi Pesisir Pascareklamsi dan Implikasinya terhadap Marginalisasi Nelayan di Pulau Serangan, Denpasar - Nyoman Suryawan (Universitas Udayana, 2015)
This article analyzes process of marginalization of SeranganIsland community in Denpasar, Bali, as a result of the island’scoastal reclamation project began in the early 1990s. The studyuses qualitative research methods whereas data collection techniquesincluded participant observation, in-depth interviews,and documentation study. Data were critically analyzed applyingsome cultural studies theories. Results of the study are asfollows. First, the form of marginalization of fishermen lookedin economic marginality, and urgency in the use environment.Second, there were external and internal factors that cause marginalization.External factors included the role of governmentthrough product legislation in force, the involvement of investorsthrough reclamation, and utilization of coastal areas for thebenefit related to tourism and other business services. Internalfactors caused by low human resource fisherman seen from hiseducation and lifestyle consumerism. Third, the marginalizationof the fisherman has a meaning of its own that is concerning themeaning of existence, the meaning of solidarity, and the meaningof life struggle.